ANALISIS SOSIO-LEGAL PERAN LEMBAGA ADAT DALAM PENYELESAIAN KONFLIK LAHAN PADA HUTAN ADAT DI WILAYAH KABUPATEN MERAUKE - Nasri Wijaya; Handika D. A. Pelu; Fransiskus Samderubun (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This research is a Socio-Legal Analysis of the Role of Customary Institutions in Resolving Land Conflicts in Customary Forests in the Merauke Regency Region, while the problems to be studied are about how the position of customary forests belonging to the Marind customary community in the Merauke Regency area is in the perspective of legislation and how the process of transitioning customary forest land by the Marind indigenous people in the Merauke Regency area. The purpose of this study was to find out how the position of the customary forest belonging to the Marind customary community in the Merauke Regency area is in the perspective of legislation and to find out the process of resolving forest land conflicts by the Marind customary community in the Merauke Regency area. The research method used in this research is Juridical Sociolegal. This research is a study that looks at law through a combination of normative analysis (legal norms, juridical) and non-legal science approaches. Based on the Papua Province Perdasus Number 23 of 2008 concerning the Ulayat Rights of Indigenous Law Communities and Individual Rights of Indigenous Peoples to the Land of the Indigenous Peoples, Marind Imbuti, the owner of customary land in the Veterans area of Merauke Regency, does not own customary forest, but owns land or customary forest. The process of transitioning the Ulayat Forest belonging to the Marind Imbuti customary community inhabiting the Merauke Regency area must go through the Customary Process and Administrative Process, both of which are quite strict and selective.